Avaliação da adequabilidade do manejo de um nitossolo por meio do índice s - Miguel, João Fernando Apel (2014)
This trial aimed at determining the S index using a drip irrigated viticulture in a nitossol. Twenty soil samples were collected for chemical analyses at the same familiar farm in Salto do Lontra city, southwestern Paraná. Richards chamber methodology was applied to make the water retention curve. Statistical process control was chosen to check which elements were under statistical control. Only three elements of the chemical properties were within control chart limits: phosphorus, calcium and aluminum. The calculated values of S index were below the critical value of S = 0.035, which means good physical condition of the soil.